POLA HULU DAN HILIR: MENEROPONG DINAMIKA EKONOMI-PERDAGANGAN DUNIA MELAYU ABAD KE XVII DAN XVIII - Ihsan Sanusi (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2017)
After the Portuguese were defeated by the Dutch, Islam became stronger as the religion of Malay Nusantara society. This is marked by the emergence of Palembang Sultanate. Palembang has been trading in Malacca, and trading and buying large quantities with Pahang. In terms of power, the Sultanate of Palembang applied different powers between upstream and downstream. In the upper reaches, the sultan and the royal authorities do not have the authority to levy taxes and recruit workers. In contrast to the upstream, downstream sultans and royal authorities have the authority to levy taxes and recruit workers. They also have a special kind of privilege, especially with regard to the right to control the results of trade. Trade orientation as part of the economic system, more visible to downstream communities. Downstream communities have long been tied to the world of commerce, can be traced since the kingdom of Srivijaya. The rivers in Palembang in addition to functioning as a means of connecting between upstream and downstream, as well as the source of basic life for the local community. The river actually contributes to shaping the mindset and "world view".